TRANSFORMING MUSIC EDUCATION IN UKRAINE: OPPORTUNITIES AND CHALLENGES IN CULTURAL AND ARTISTIC EDUCATION REFORM - ZAKUS, Ihor; LEBEDIEVA, Nataliia; GVINIASHVILI, Irma; KORZHENOK, Viktoriya; ADU, Dennis (Studia Universitatis Babes-Bolyai Musica, 2025)
The article discusses the current challenges and prospects for developing music education in Ukraine while reforming the cultural and artistic sphere. Particular attention is paid to the role of grant funding as an effective tool for supporting educational initiatives, which allows for the preservation of cultural infrastructure and ensures the stability of the educational process in the context of limited resources. The study uses methods of financial analysis, comparison of regional differences in financing the cultural and educational sphere, and synthesis and generalization of cultural development strategies in Ukraine, which allowed the creation of a holistic view of state-of-the-art education. Particular attention is paid to analyzing the legal framework that regulates the activities of arts education institutions. The key barriers and opportunities for adapting Ukrainian music education to European standards were identified. The study results showed that grant support plays a significant role in preserving curriculum and creating new projects even during the war. In the future, it is planned to develop practical recommendations for improving the financing and management of cultural and educational institutions. An important area for further research is to assess the long-term impact of grant programs on increasing the competitiveness of Ukrainian art education in the international arena.